"Cake is not an Attack on Democracy": Moving beyond Carceral Pride and Building Queer Coalitions in Post–22/7 Norway. Issue 4 (2nd October 2021) - Engebretsen, Elisabeth L.
ABSTRACT: The pieing of a far-right politician at the 2016 Oslo Pride parade was met with condemnation from the media and within Norway's LGBT movement. The pie-thrower, a member of the European queer-anarchist band Cistem Failure, was charged with committing an "attack on democracy, " a part of the criminal code strengthened after the 22/7 terrorist attacks in 2011 and sentenced to imprisonment followed by deportation. This article reflects critically on the dominant narratives of this event as well as Pride politics more generally, and places them in context with Norway's increasing mainstreaming of right-wing populism and liberal LGBT organizations' dependence on state protection and inclusion policies. Drawing on Emma Russell's critical historical and queer optic, Jin Haritaworn's regenerative analytic, and Cistem Failure's alter-narratives, I argue that Norway's growing "security governance" promotes a divisive othering and obscures the violent exclusion of "undeserving" queers; this presents a deeply disturbing challenge to the democratic right to protest and public dissent. In turn, I advocate for the urgency of a transformative, coalitional politics of radical care - unafraid of confrontation and refusal, committed to the everyday acts of leaving nobody behind and to envisioning a world otherwise.